1998
DOI: 10.1097/00000539-199809000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of Isoflurane Effects on Left and Right Ventricular Afterload and Hydraulic Power Generation in Swine

Abstract: In this study, we examined the effects of isoflurane on cardiac performance in swine and found that, although the drug depresses contraction of both the left and right ventricles similarly, it has different effects on forces that oppose the ejection of blood. These findings demonstrate that the two interdependent pumps that comprise the heart can be influenced differently by anesthetic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…16,[27][28][29] Previous studies reported that halothane, enflurane, and isoflurane decreased RV contractility in a dose-related manner. 7,9,11 Isoflurane deteriorated RV function more than LV function because it decreased LV afterload but did not affect RV afterload. 8,11 In a previous study, we noted that dogs receiving propofol during pulmonary embolism tolerated the procedure, whereas those receiving isoflurane had RV failure and died.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,[27][28][29] Previous studies reported that halothane, enflurane, and isoflurane decreased RV contractility in a dose-related manner. 7,9,11 Isoflurane deteriorated RV function more than LV function because it decreased LV afterload but did not affect RV afterload. 8,11 In a previous study, we noted that dogs receiving propofol during pulmonary embolism tolerated the procedure, whereas those receiving isoflurane had RV failure and died.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Authors also noted a better preservation of left ventricular performance with isoflurane than with halothane. 2,4 The effects of inhalational anesthetics on right ventricular (RV) contractility have been studied much less, [7][8][9][10][11] but at least two studies reported different effects on right and left ventricular performance and afterload. 8,11 Desflurane is a recent halogenated anesthetic, with short duration of action due to its low tissue solubility and negligible biotransformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, chemical restraint or anaesthesia are often needed for even minor procedures. Conversely, anaesthesia can be the prime objective for the study, for example to examine the effects of anaesthetics before clinical use (Weiskopf et al, 1989;Laber-Laird et al, 1992;Weiskopf et al, 1992;Heerdt et al, 1998;Kerbaul et al, 2000), to assess different anaesthetic protocols (Clutton et al, 1997) or to evaluate the impact of anaesthetic on a poisoned individual (Duncan et al, 2001).…”
Section: Some Issues Raised By the Use Of Anaesthesiamentioning
confidence: 99%
“…The cardiovascular actions of isoflurane in the swine are similar to those in humans (Weiskopf et al, 1992). For example, isoflurane will cause depression of left and right ventricle contraction of the heart in swine (Heerdt et al, 1998). Another halogenated anaesthetic, halothane, causes a marked decrease in cardiac output and reduces mesenteric blood flow to less than half the value of non-anaesthetized swine (Loick et al, 1991).…”
Section: Pressor Effects Of Na and Anaesthesiamentioning
confidence: 99%